ISLAMIC BANKING MARKET DISCIPLINE IN INDONESIA - Joko Suliyono; Tastaftiyan Risfandy (Bank Indonesia, 2021)
This paper examines the market discipline of Islamic banks, as manifested by the responses of depositors with regard to their deposits and profit-sharing ratio to the fundamentals of the banks in the case of Indonesia. We analyse the supply and demand function of deposits using panel data from 10 Islamic banks from 2010 Q1 to 2019 Q4. We empirically find that market discipline in Indonesian Islamic banks is relatively weak, and conjecture that this is for two reasons. First, religious depositors have driven the unusual behaviour of Islamic banks, as we find that they stay with the same bank, even if it has poor fundamental conditions. Second, the profit and loss sharing mechanism means that Islamic bank depositors do not have great flexibility in demanding a higher rate relevant to the risk they must bear. This is because depositors' actual return is set to be consistent with the actual profit obtained from the banks' lending activities. Our results lead to the call for policymakers to effectively monitor the fundamental conditions of Islamic banks and to collaborate with agencies and organisations that promote Islamic bank development in Indonesia.